2009
DOI: 10.1111/j.1752-1688.2009.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a SWAT Patch for Better Estimation of Sediment Yield in Steep Sloping Watersheds1

Abstract: The watershed scale Soil and Water Assessment Tool (SWAT) model divides watersheds into smaller subwatersheds for simulation of rainfall-runoff and sediment loading at the field level and routing through stream networks. Typically, the SWAT model first needs to be calibrated and validated for accurate estimation through adjustment of sensitive input parameters (i.e., Curve Number values, USLE P, slope and slope-length, and so on). However, in some instances, SWAT-simulated results are greatly affected by the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The SWAT model simulations are another source of uncertainty, due to difficulty in using the model to estimate sediment transport. As a number of researchers have pointed out [13,33,34,43,70] SWAT has limitations in representing the short, rapid rainfall-runoff events that typically occur in small catchments, such as Corbeira, and that will probably increase in the future. Moreover, MUSLE, the method used in SWAT to estimate sediment yield, does not include the characteristics of events, such as the erosive power or duration of rainfall, which might result in model error for assessing erosion, because these variables affect soil detachment by raindrops and transport of detached particles by runoff.…”
Section: Effects Of Simultaneous Changes In Climate Parameters In Susmentioning
confidence: 99%
“…The SWAT model simulations are another source of uncertainty, due to difficulty in using the model to estimate sediment transport. As a number of researchers have pointed out [13,33,34,43,70] SWAT has limitations in representing the short, rapid rainfall-runoff events that typically occur in small catchments, such as Corbeira, and that will probably increase in the future. Moreover, MUSLE, the method used in SWAT to estimate sediment yield, does not include the characteristics of events, such as the erosive power or duration of rainfall, which might result in model error for assessing erosion, because these variables affect soil detachment by raindrops and transport of detached particles by runoff.…”
Section: Effects Of Simultaneous Changes In Climate Parameters In Susmentioning
confidence: 99%
“…Zhang et al, 2013). Concerning the SWAT method, Kim et al (2009) suggested modifying the SWAT GIS pre-analysis for assessing hillslope length, especially if average slope in the watershed is > 25%. Yao et al (2010) assessed the effect of 10-and 30-m DEM pixel size on hillslope length estimations using two GIS-methods (Flow Length and Flow accumulation) to see which of them resulted in hillslope length most similar to observed field measures.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research results showed that the uncertainty of the watershed partitioning level had a particularly obvious impact on the runoff, sediment, and other variables (Larose et al 2007;Kim et al 2009;Han et al 2014). Meanwhile, the hydrological model is a high dimensional complex mathematical equation set model.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted by researchers to explore the influence of the watershed partitioning level on the performance of the hydrological models (e.g., Larose et al 2007;Kim et al 2009). Norris and Haan (1993) divided a watershed with an area of 31.08 km 2 into three levels and found that the difference between the flood peak flow simulated by only one sub-basin, and the other two simulated values were over 35%.…”
Section: Introductionmentioning
confidence: 99%